Heartbeat - Steel, Danielle (London : Corgi Books, 1992)
Bill Thigpen, writer producer of the No.1 daytime TV drama was so busy watching his career soar that he never noticed his marriage collapse. Now, nine years later, living alone in Hollywood, even without his wife and kids, his life and success are still reasonably sweet. Top-of-the-chart ratings, good-natured casual affairs, and special vacations with his two young sons. His life is in perfect balance, he thinks. Adrian Townsend thought she had everything: a job she liked as a TV production assistant and a handsome husband who was a rising star in his own field. In as enviable life they'd worked hard for--the American Dream. Until she got pregnant. Suddenly all she had was chaos. And Steven's ultimatum. Him or the baby.
Keywords: Television producers and directors -- Fiction; Love stories